2018
DOI: 10.3390/ma11040647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reaction Temperature on Structure, Appearance and Bonding Type of Functionalized Graphene Oxide Modified P-Phenylene Diamine

Abstract: In this study, graphene oxides with different functionalization degrees were prepared by a facile one-step hydrothermal reflux method at various reaction temperatures using graphene oxide (GO) as starting material and p-phenylenediamine (PPD) as the modifier. The effects of reaction temperature on structure, appearance and bonding type of the obtained materials were investigated by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), and scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(51 reference statements)
2
3
0
Order By: Relevance
“…To demonstrate that the organic molecules are covalently grafted onto graphene, many measures have been adopted, such as FT-IR, XRD, and XPS. As shown in Figure a, for the PRG material, the characteristic peak of the amide carbonyl group at 1643 cm –1 and the stretching vibrations of the N–H and C–N bonds at 1497 and 1396 cm –1 indicate that an amidation reaction has occurred between PPD and GO . The same conclusion can be proven by XPS spectra of PRG.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…To demonstrate that the organic molecules are covalently grafted onto graphene, many measures have been adopted, such as FT-IR, XRD, and XPS. As shown in Figure a, for the PRG material, the characteristic peak of the amide carbonyl group at 1643 cm –1 and the stretching vibrations of the N–H and C–N bonds at 1497 and 1396 cm –1 indicate that an amidation reaction has occurred between PPD and GO . The same conclusion can be proven by XPS spectra of PRG.…”
Section: Resultssupporting
confidence: 65%
“…As shown in Figure 2a, for the PRG material, the characteristic peak of the amide carbonyl group at 1643 cm −1 and the stretching vibrations of the N−H and C−N bonds at 1497 and 1396 cm −1 indicate that an amidation reaction has occurred between PPD and GO. 45 The same conclusion can be proven by XPS spectra of PRG. In Figure 2d, C For the PRG@NDI-2 material, intense absorption peaks observed at 1710 and 1660 cm −1 are indicative of the carbonyl groups within the polyimide (Figure 2a).…”
Section: Resultssupporting
confidence: 59%
“…Accordingly, the representative signals at 399.5 eV and 401.0 eV correspond to the NH-C] O and C-N groups respectively. [48][49][50] The wide scan XPS spectra of GO (i) and T-GO (ii) shown in Fig. 3(b) conrm the functionalization of tyramine on GO from the additional signal corresponding to N appearing in T-GO.…”
Section: Resultsmentioning
confidence: 99%
“…E. Rodriguez-Acevedo et al [20] demonstrated that shallow reservoirs could be effective for carbon capture after injecting nanofluids based on N-rich carbon nanospheres. Finally, the last articles of this Special Issue deal with the development of N-doped graphene films for high sensitivity electrodes [21]; the functionalization of graphene oxides with p-phenylenediamine as a modifier [22]; and the induction of magnetic moments in graphene by introducing sp 3 -defects [23].…”
mentioning
confidence: 99%